Psychosocial risk factors associated with suicide in youth and adolescents: A systematic review (2022)
The phenomenon of suicide is a worldwide problem that has been increasing in the last decade with greater prevalence in the adolescent and young population, generating impact in different contexts such as family, social, economic, and educational, among others. That is why this systematic review focuses on identifying psychosocial factors associated with suicidal behavior in adolescents and young people, in publications published worldwide. This will allow us to recognize within these studies the coincidence of different aspects, within which the following psychosocial factors are highlighted: family, exposure to various forms of violence, risk behaviors, psychopathology, and negative emotional states. The bibliographic review carried out confirms the multifactorial dynamics of suicide attempts and completed suicides. Suicide, besides being a complex phenomenon to approach, has equally complex predictability. However, it is still possible to develop strategies to warn or prevent the behavior in a timely manner. Thus, the findings invite us to have a holistic view of the phenomenon and to aim from different angles to counteract the risk factors that predispose us to such behavior.